(untitled) (Journal of Economic Research & Business Administration, 2016)
In the context of contemporary realities of the Kazakhstan business relevance perspective of strategic analysis as an essential tool for effective strategic management of business entities has increased steadily. Strategic analysis has been regarded by scientists as a traditional function of strategic management. However, strategic analysis must be not so much a superficial study of the strengths and weaknesses of the company, as detailed diagnostics strategic position compared to the competition and the orientation for the future. Therefore, in this article the methodology of strategic economic analysis was considered, in particular, Porter five forces model, SWOT – analysis and analysis of strategic groups of competitors have been applied on the example of the pharmaceutical industry in Kazakhstan. Thus, the work has proved the importance of the strategic economic analysis as a key factor in ensuring the sustainability of enterprises.